Designing Policy Solutions to Build a Healthier Rural America. Issue 3 (2020) - Vohra, Sameer; Pointer, Carolyn; Fogleman, Amanda; Albers, Thomas; Patel, Anish; Weeks, Elizabeth
Abstract : Disparities exist in the health, livelihood, and opportunities for the 46-60 million people living in America's rural communities. Rural communities across the United States need a new energy and focus concentrated around health and health care that allows for the designing capturing, and spreading of existing and new innovations. This paper aims to provide a framework for policy solutions to build a healthier rural America describing both the current state of rural health policy and the policies and practices in states that could be used as a national model for positive change.